2011
DOI: 10.1186/1471-230x-11-64
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a probiotic fermented milk in the gut ecosystem and in the systemic immunity using a non-severe protein-energy-malnutrition model in mice

Abstract: BackgroundMalnutrition affects the immune response, causing a decrease of defence mechanisms and making the host more susceptible to infections. Probiotics can reconstitute the intestinal mucosa and stimulate local and systemic immunity. The aim of this work was evaluate the effects of a probiotic fermented milk as a complement of a re-nutrition diet, on the recovery of the intestinal barrier, and mucosal and systemic immune functions in a murine model of non-severe protein-energy-malnutrition. Its potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…casei DN‐114‐001 (10 8 CFU ml −1 ) in nonsevere protein‐energy‐malnutrition mice model, all the test groups showed similar values for goblet cells without significant differences compared with both control groups (malnourished and well‐nourished) (Galdeano et al . ). The intestinal villi of malnourished control group were short and their numbers were lower than in the well‐nourished and Lact.…”
Section: Mucosal Immune Systemmentioning
confidence: 97%
See 3 more Smart Citations
“…casei DN‐114‐001 (10 8 CFU ml −1 ) in nonsevere protein‐energy‐malnutrition mice model, all the test groups showed similar values for goblet cells without significant differences compared with both control groups (malnourished and well‐nourished) (Galdeano et al . ). The intestinal villi of malnourished control group were short and their numbers were lower than in the well‐nourished and Lact.…”
Section: Mucosal Immune Systemmentioning
confidence: 97%
“…casei DN‐114‐001 (10 8 CFU ml −1 ), presented the increase in phagocytic activity of macrophages isolated from peritoneum and spleen (Galdeano et al . ).…”
Section: Systemic Immune Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…Thirdly, probiotics stimulate the mucosal immune system in the patient's intestinal tract to secrete protective immunoglobulins (Ig) such as secretory IgA and protective defensins, and they produce bacteriocins into the lumen [82]. It has also been shown that Lactobacillus brevis and Streptococcus thermophilus selectively stimulate apoptosis of mucosal immune cells counteracting the excessive accumulation of these cells in the gut [83].…”
Section: Effects Of Probiotics On Uc Remission and Pathogenesismentioning
confidence: 99%